2016
DOI: 10.1002/cncr.29892
|View full text |Cite
|
Sign up to set email alerts
|

Management of localized and advanced prostate cancer in Canada: A lifetime cost and quality‐adjusted life‐year analysis

Abstract: BACKGROUND:To the authors' knowledge, the literature to date lacks studies examining lifetime costs and quality-adjusted life-years (QALYs) of prostate cancer (PCa) management strategies that integrate localized and advanced disease. The objective of the current study was to assess lifetime costs and QALYs associated with contemporary PCa management strategies across risk groups by integrating localized and advanced disease. METHODS: The authors' validated Markov chain Monte Carlo model was used to predict lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 42 publications
0
14
0
4
Order By: Relevance
“…Prostate biopsies and management of postprocedure complications accounted for 72% of the total cost. The economic burden of screening must be weighed against the potential cost savings of earlier diagnoses as studies have shown a direct correlation between treatment cost per patient and the risk group at time of diagnosis [ 22 23 ]. One way to assess the cost effectiveness of PSA screening is to assess the value added by various screening strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate biopsies and management of postprocedure complications accounted for 72% of the total cost. The economic burden of screening must be weighed against the potential cost savings of earlier diagnoses as studies have shown a direct correlation between treatment cost per patient and the risk group at time of diagnosis [ 22 23 ]. One way to assess the cost effectiveness of PSA screening is to assess the value added by various screening strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of TAMs in prostate cancer progression has been evaluated in several studies (Craig et al 2008;Gannon et al 2009;Nonomura et al 2011;Fujii et al 2013;Gollapudi et al 2013;Lanciotti et al 2014) and is consistent with the protumorigenic effects of TAMs observed in other cancer types; some studies suggest a link between TAMs and disease recurrence (Gannon et al 2009;Nonomura et al 2011). Craig et al 2008;Gannon et al 2009;Nonomura et al 2011;Gollapudi et al 2013;Lanciotti et al 2014;Escamilla et al 2015;Gao et al 2017;Maolake et al 2017 Mouse: (Gleason 3 + 3) are typically managed by active surveillance, as large randomized clinical trials show no mortality differences between active surveillance and radical prostatectomy or radiotherapy (Iversen et al 1995;Wilt et al 2012;Bill-Axelson et al 2014;Hamdy et al 2016;Sanyal et al 2016;Wilt et al 2017). At the other end of the spectrum are high-risk cancers (Gleason ≥8), which receive more aggressive treatment, including surgery and radiation-based therapies.…”
Section: Cellular Heterogeneity In the Tmementioning
confidence: 60%
“…For example, the current standard diagnostic test for prostate cancer that measures prostate specific antigen (PSA) levels in patient blood samples, has low specificity for early detection of prostate cancer, resulting in the overdiagnosis and overtreatment of men for this cancer [98]. However, newly developed tests that use patient-specific genetic data for early diagnosis and accurate stratification of low-risk/indolent versus high-risk/metastatic prostate cancer have led to better patient outcomes and high cure rates in clinical trials [99][100][101]. Use of these genetic data-based tests in clinical practice will represent personalized medical treatment of prostate cancer.…”
Section: Expert Opinionmentioning
confidence: 99%